2020
DOI: 10.1038/s41598-020-64314-8
|View full text |Cite
|
Sign up to set email alerts
|

The SIRS criteria have better performance for predicting infection than qSOFA scores in the emergency department

Abstract: Kiyotsugu takuma 14 , Kazuma Yamakawa 15 & the Japanese Association for Acute Medicine (JAAM) Sepsis prognostication in intensive care Unit and emergency Room (Spice) (JAAM Spice) Study Group* Systemic inflammatory response syndrome (SIRS) reportedly has a low performance for distinguishing infection from non-infection. We explored the distribution of the patients diagnosed by SIRS (SIRS patients) or a quick sequential organ failure assessment (qSOFA) (qSOFA patients) and confirmed the performance of the both … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 19 publications
3
34
0
Order By: Relevance
“…Since the SOFA score consists of much more detailed intensive care variables than the qSOFA score and the SIRS criteria, the speci city is higher, but sensitivity remains low. These arguments are in accordance with the ndings of Gando et al as well as Krebs et al, who demonstrated that the SIRS criteria, SOFA score, and qSOFA score were not able to predict sepsis in the emergency department or surgical ICU [18,26].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Since the SOFA score consists of much more detailed intensive care variables than the qSOFA score and the SIRS criteria, the speci city is higher, but sensitivity remains low. These arguments are in accordance with the ndings of Gando et al as well as Krebs et al, who demonstrated that the SIRS criteria, SOFA score, and qSOFA score were not able to predict sepsis in the emergency department or surgical ICU [18,26].…”
Section: Discussionsupporting
confidence: 90%
“…Another study showed that these scores are also not able to predict infection in the emergency room [26]. Based on the ndings of our study, the use of the qSOFA score as a predictor of mortality can be supported, while its predictive power for the detection of sepsis can be doubted in postsurgical IMCU patients, which might be caused by surgery-induced systemic in ammation.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Another study showed that these scores are also not able to predict infection in the emergency room [26].…”
Section: Discussionmentioning
confidence: 99%
“…Satisfying the two minimum criteria for a SIRS diagnosis is relatively common in some infectious or non-infectious diseases (i.e., pancreatitis or trauma) [ 10 ]. However, the importance of assessing the presence of these factors has generated different results and, at the very least, they are intriguing due to the evident selectivity in terms of when and where they are most useful [ 11 ].…”
Section: Introductionmentioning
confidence: 99%